2022
DOI: 10.54112/bcsrj.v2022i1.132
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Who Guidelines of Management of Severe Acute Malnutrition in Children 6 Months to 5 Years

Abstract: To evaluate the management of severe acute malnutrition according to WHO guidelines in children. A prospective study was conducted at Paediatrics Department of Mother and Children Complex DHQ Hospital Sheikhupura from August 2021- August 2022. A total of 200 children with age range between 6 months and 5 years were included in the study. Personal information of patients was supposed to be recorded along with malnutrition classification, diagnostic signs, treatment and its outcomes according to the WHO guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In this study, an attempt for making Mobile size measurer is designed that overcomes the challenges imposed by other different existing models being used for mobile application size estimation process [1,2]. This paper has demonstrated COSMIC Plus measurement procedure for sizing functional requirements of mobile applications using UML representations.…”
Section: Prediction Of Functional Size Of Mobile Application 10 Concl...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, an attempt for making Mobile size measurer is designed that overcomes the challenges imposed by other different existing models being used for mobile application size estimation process [1,2]. This paper has demonstrated COSMIC Plus measurement procedure for sizing functional requirements of mobile applications using UML representations.…”
Section: Prediction Of Functional Size Of Mobile Application 10 Concl...mentioning
confidence: 99%
“…Thus, effort estimation, has acquired a huge importance in software development process as it depicts whether the project development is going in a profit or loss. The reviewed research papers [1,2] advocates the effectiveness of COSMIC FP for Mobile application size estimation. However, it was reported that the popularity of COSMIC FP was not enough to quantify it as a standard approach for mobile application effort estimation.…”
Section: Introductionmentioning
confidence: 99%